Winter diet of Blue-winged Teal Anas discors, Green-winged Teal Anas carolinensis, and Northern Shoveler Anas clypeata in east-central Texas - Collins, Daniel P.; Conway, Warren C.; Mason, Corey D.; Gunnels, Jeffrey W. (Wildfowl, 2017)
Whilst dabbling duck diet has been studied in some detail on the breeding grounds, it has not been studied as exhaustively at wintering sites in North America. We therefore aimed to describe the diet of Blue-winged Teal Anas discors, Green-winged Teal Anas carolinensis, and Northern Shoveler Anas clypeata using moist-soil managed wetlands in east-central Texas by determining from gut samples the food items ingested and the variation in dry mass of each item taken. A variety of 33 food items (mostly seeds and invertebrates, with only trace amounts of other plant material) were recorded in gut samples of 174 birds. Aggregate dry mass varied among and between species and age-sex cohorts. Several food items occurred frequently in each of the three species – most notably knotweed Polygonum sp., panic grass Panicum sp., Water-pepper Persicaria hydropiper and Curly Dock Rumex crispus – indicating the importance of these plant seeds, along with Gastropods, in the diet of dabbling ducks wintering on the wetlands of east-central Texas.